The Use of Hebrew and Aramaic in the Greek New Testament - Mussies, Gerard (New Testament studies, 1984)
It is not our purpose to re-open the discussion on the linguistic character of the different Semitic elements in the New Testament and to go into the problem whether a particular word spoken by Jesus such as εφφαθα is either Hebrew or Aramaic. Neither do we again want to raise the question of how many languages Jesus could speak or understand and which of these he normally used.1 Finally it is also not our intention to ascertain the exact meaning of such a debated phrase as Mαραναθά, whether this is ‘our Lord has come’ or ‘our Lord, come’.